What is the protective effect of krill oil on rat ovary against ischemia–reperfusion injury?. Issue 3 (28th November 2018) - Yeral, Ilkin; Sayan, Cemile D.; Karaca, Gökhan; Simsek, Yavuz; Sagsoz, Nevin; Ozkan, Zehra S.; Atasoy, Pınar; Sahin, Yasar; Neselioglu, Salim; Erel, Ozcan
Abstract: Aim: In this study, we aimed to investigate the protective effect of krill oil (KO) against ischemia–reperfusion (I/R) injury on rat ovary. Methods: This study was conducted with 32 Wistar Albino rats. Rats were divided into four groups, with eight rats in each group‐as follows: Sham group, I/R group, I/R + low dose KO group (50 mg) and I/R + high dose KO group (500 mg). The histopathological and follicle counts were performed on the right ovary. The total antioxidant status, total oxidant status and oxidative stress index were evaluated on the left ovary. And also serum N‐thiol level, serum T‐thiol level, serum disulfide (SDS) level, serum disulfide/N‐thiol and serum disulfide/T‐thiol ratios were evaluated too. Results: A statistically significant difference was determined between the I/R group and all the other groups for all parameters. There was significant difference between KO groups and the Sham group for the parameters of serum N‐thiol, serum T‐thiol, SDS, serum disulfide/N‐thiol and serum disulfide/T‐thiol. SDS, total oxidant status and oxidative stress index were determined to be the highest in the I/R group and the lowest in the low dose KO group. The total antioxidant status values were found to be the highest in the high dose KO group and the lowest in the I/R group. Follicle counts and histological injury scores showed no significant difference between Sham and KO groups. Conclusion: This study demonstrated that KO has beneficial effects on decreasing the injury after I/R on rat ovary.